Layerwise generalized formulation solved via a boundary discontinuous method for multilayered structures. Part 1: Plates - Laureano Ronaldo Walter; Mantari José Luis (Curved and Layered Structures)
This article presents for the very first time a layerwise bending analytical solution for cross-ply laminated composite plates with clamped boundary conditions at all edges. The displacement field is implemented within the framework of the Carrera unified formulation at a layer level by employing Legendre polynomials. The governing equations are obtained by using the principle of virtual displacements statement. This work utilizes the boundary-discontinuous double Fourier series to provide analytical solutions. The high accuracy of the proposed solution is demonstrated by comparing the results with three-dimensional finite-element model (FEM) solutions of multilayered and sandwich plates for various side-to-thickness ratios. In conclusion, the highly accurate proposed solution might be used as a benchmark problem for new analytical or FEMs.